2015
DOI: 10.1007/s10753-015-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

CD4+, CD25+, FOXP3+ T Regulatory Cell Levels in Obese, Asthmatic, Asthmatic Obese, and Healthy Children

Abstract: The aim of this prospective case control study is to determine CD4(+), CD25(+), and FoxP3(+) T regulatory cells (Tregs) and T helper cells (Ths) in obese, asthmatic, asthmatic obese, and healthy children. Obese (n = 40), asthmatic (n = 40), asthmatic obese (n = 40), and healthy children (n = 40) were included in this study. Blood samples collected from children were marked with CD4, CD25, ve Foxp3 in order to detect Tregs and Ths by flow cytometric method. Statistical analyses were performed. p ≤ 0.05 was chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Accordingly, it has been shown that children who were obese, asthmatic, and, asthmatic-obese present significant lower circulating regulatory T cells (Tregs) compared to healthy controls. Tregs have been shown to encourage neutrophil apoptosis, improve efferocytosis, and produce specific cytokines [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it has been shown that children who were obese, asthmatic, and, asthmatic-obese present significant lower circulating regulatory T cells (Tregs) compared to healthy controls. Tregs have been shown to encourage neutrophil apoptosis, improve efferocytosis, and produce specific cytokines [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…T cell immunity plays important roles in chronic inflammatory diseases such as obesity. Decreased regulatory T cells status is noted in obese children [3] .…”
Section: Introductionmentioning
confidence: 94%
“… 77 78 Concepts of regulatory B cells are being investigated for their role in suppressing T cell-independent activation of B cells with self-reactive B cell receptors (BCRs) 79 and IL-10-mediated regulation of autoimmune responses. 80 In context to asthma, there is evidence of both compromised peripheral tolerance in severe asthmatics with significant low levels of Foxp3 + -Treg cells 81 82 and reduced IL-10 expression. 81 83 Furthermore, CD25 + CTLA4 + Foxp3 + -T cells with regulatory functions were enumerated to be significantly reduced in induced sputum from atopic asthmatics compared to healthy volunteers.…”
Section: Working Hypothesis Of Autoimmune-associated Asthma Pathogenementioning
confidence: 99%
“… 80 In context to asthma, there is evidence of both compromised peripheral tolerance in severe asthmatics with significant low levels of Foxp3 + -Treg cells 81 82 and reduced IL-10 expression. 81 83 Furthermore, CD25 + CTLA4 + Foxp3 + -T cells with regulatory functions were enumerated to be significantly reduced in induced sputum from atopic asthmatics compared to healthy volunteers. 84 Again, none of these studies investigated autoantibodies and therefore neither association nor causality can be derived.…”
Section: Working Hypothesis Of Autoimmune-associated Asthma Pathogenementioning
confidence: 99%